(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article examines the main pathways of implementing digital technologies in education, analyzing current trends, challenges, and opportunities. The research focuses on theoretical frameworks and literature analysis to identify effective strategies for digital transformation in educational settings.